Long-term follow-up of acute and chronic non-A, non-B post-transfusion hepatitis: evidence of progression to liver cirrhosis. Issue 4 (April 1982) - Realdi, G; Alberti, A; Rugge, M; Rigoli, A M; Tremolada, F; Schivazappa, L; Ruol, A
Abstract : The long-term outcome of non-A, non-B post-transfusion hepatitis was evaluated in 21 patients who developed the illness after open-heart surgery and could be followed thereafter up to five years. Histological chronic sequelae were documented in 13 patients, and consisted of chronic persistent hepatitis in one case, chronic lobular hepatitis in two and chronic active hepatitis in 10, five of whom also developed superimposed cirrhosis. Progression to these chronic states was in most cases symptomless, independently of the severity of liver lesions; one patient, however, died of gastrointestinal bleeding due to cirrhosis of the liver. During follow-up the biochemical pattern of chronic non-A, non-B hepatitis was unique, while striking fluctuations of transaminase levels. Liver histology proved essential to identify the severity of chronic liver lesions, as clinical and biochemical features were uniform and not indicative of it. Our results suggest that cirrhosis may develop, often with an asymptomatic course, in a significant number of patients who do not recover after acute post-transfusion non-A, non-B hepatitis.